The Mediation Effect Firm Performance on Green Innovation and Firm Value: Evidence the Mining Industry - Yuniarti, Rina; Isnalita, Noorlailie Soewarno,; H Habiburrochman, Meilaty Finthariasari, (Opción)
Global warming is currently an issue that is widely discussed both the accounting literature and others. The topic of environmental performance is gaining increasing attention from academics and politics when it is associated with each country’s policies regarding environmental damage. This article to investigate both the direct and indirect the effect of green innovation and firm value on financial performance as mediating variable. The authors find that the green innovation has a positive effect on the firm value and financial performance full mediate the effect green innovation and firm value